M13 phage DNA as a universal marker for DNA fingerprinting of animals, plants and microorganisms - Ryskov, A P; Jincharadze, A G; Prosnyak, M I; Ivanov, P L; Limborska, S A (FEBS letters, 1988)
Hypervariable polymorphic patterns were detected with M13 phage DNA as a probe in genomic DNA of organisms belonging to different taxonomic groups including animals (vertebrates and invertebrates), plants and microorganisms. Individual-specific restriction pattern analysis (DNA fingerprinting) with this probe proved to be useful for individual identification, analysis of somatic stability and paternity testing in man. The nuclear type of inheritance indicates that the hypervariable DNA regions in question are located in the chromosomes, not in the mitochondrial DNA. The data obtained also demonstrate a potential range of M13 DNA applications as a probe for DNA fingerprinting of animals, plants and microorganisms, particularly for the determination of inbred lines, identification of bacterial strains and establishing stock, variety and strain distinctions.